Are Freshwater Snails, Melanoides sp. and Invasive Tarebia granifera (Gastropoda: Thiaridae) Suitable Intermediate Hosts for Calicophoron microbothrium (Trematoda: Paramphistomoidea)? An Experimental Study - Malatji, Mokgadi P.; Myende, Nkululeko; Mukaratirwa, Samson (Frontiers in Veterinary Science, 2021)
Snails and adult amphistomes were collected from water bodies and abattoirs respectively in Mpumalanga province of South Africa. They were identified to species level using morphological and molecular techniques. The amphistomes were identified based on morphological characters as well as the ITS-1/5.8S/ITS-2 marker as C. microbothrium and the snails as Melanoides spp. and Tarebia granifera based on the 16S and ITS-2 markers. Snails were bred to F1 generation under laboratory conditions. Ninety snails were randomly selected from the laboratory bred F1 snails and 25 Melanoides sp. and 20 T. granifera were exposed to C. microbothrium miracidia and the same numbers were maintained as non-exposed control. Results showed that C. microbothrium successfully established in Melanoides spp. and produced cercariae, and the pre-patent period recorded was 21 days. Three snails did shed cercariae at day 21 post-exposure (PE) and one was found with rediae and free cercariae in the soft tissues on dissection at day 44 PE. The same parasite did not establish in T. granifera. Melanoides sp. started producing offspring at day 7 PE, whilst T. granifera only started reproducing at day 14 PE, and the difference in number of offspring produced per week were significant (P < 0.05) at 28 days and 35 days PE. In conclusion, our results showed that Melanoides spp. is a suitable intermediate host for C. microbothrium and given the wide distribution of this snail species, it is important to determine its role in the natural transmission of other Calicophoron species which have been reported in South Africa.